2006
DOI: 10.1111/j.1365-2222.2006.02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotriene receptor 1 promoter polymorphism is associated with aspirin‐intolerant asthma in males

Abstract: SummaryBackground Cysteinyl leukotrienes (CysLTs) play important roles in the pathogenesis of eosinophilic airway inflammation characterized by bronchoconstriction, mucus secretion and airway hyper-responsiveness via cysteinyl leukotriene receptor 1 (CysLTR1)-mediated mechanism. CysLTR1-selective antagonists have anti-bronchoconstrictive and antiinflammatory effects in asthma, particularly aspirin-intolerant asthma (AIA). Methods To investigate the association of CysLTR1 with AIA development, we identified thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 34 publications
2
68
1
2
Order By: Relevance
“…In a Caucasian Spanish population, Sanz et al reported the minor allele of the synonymous coding SNP 927 T>C (rs320995) to be associated with asthma (130 asthma vs 78 controls) (123), but Arriba-Mendez et al observed this association only in male subjects (87 asthma vs 79 controls, p < 0.008) (128), whereas two other groups could not detect any association in a Caucasian British and a Korean population (109,129). Although this was not reproduced in a Japanese study (137 families) (130), Kim et al found an association of the three SNPs in the CYSLTR1 promoter with aspirin intolerant asthma among male Koreans (340 individuals, p < 0.03) (131). The authors also observed an association of these same alleles with atopy among female aspirin intolerant asthmatic individuals (p = 0.03) (131).…”
Section: Cyslt Receptorsmentioning
confidence: 97%
See 2 more Smart Citations
“…In a Caucasian Spanish population, Sanz et al reported the minor allele of the synonymous coding SNP 927 T>C (rs320995) to be associated with asthma (130 asthma vs 78 controls) (123), but Arriba-Mendez et al observed this association only in male subjects (87 asthma vs 79 controls, p < 0.008) (128), whereas two other groups could not detect any association in a Caucasian British and a Korean population (109,129). Although this was not reproduced in a Japanese study (137 families) (130), Kim et al found an association of the three SNPs in the CYSLTR1 promoter with aspirin intolerant asthma among male Koreans (340 individuals, p < 0.03) (131). The authors also observed an association of these same alleles with atopy among female aspirin intolerant asthmatic individuals (p = 0.03) (131).…”
Section: Cyslt Receptorsmentioning
confidence: 97%
“…In a high prevalence asthmatic population with a founder effect, Thompson et al observed the minor allele of the coding polymorphism 899 G>A (Gly300Ser) to be associated with both asthma (p = 0.005) and atopy (OR = 4; 95% CI:1.2-13.3) in female subjects (132). Other studies have detected an association of the promoter or coding SNPs with allergic phenotypes such as high total IgE (p = 0.003) (131) and AD (OR = 4.97; 95% CI:1.29-19.13) (128), which could not be reproduced elsewhere (129,130). Overall, despite these discrepancies, most studies agree that there is an association between CYSLTR1 genetic variation and allergic phenotypes and that this association is gender specific.…”
Section: Cyslt Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 2×10 5 cells were seeded in 24-well plates and transfected with 0.5 μg of the reporter constructs and 0.5 μg of pSV-β-galactosidase control vector using a microporator (Incyto, Suwon, Korea) at 1,300 V and pulse width of 30 ms. At 48 h posttransfection, the cells were lysed and assayed for firefly luciferase activity according to the manufacturer's instructions (Promega). The transfections and luciferase assays were repeated four times (twelve times in total) according to the method described previously [19].…”
Section: Study Subjectsmentioning
confidence: 99%
“…The bronchoconstrictive effects of CysLTs are exerted via their G-coupled receptor, CysLT receptor type 1 (CysLTR1) [18], and these effects can be efficiently reversed by CysLTR1 antagonist [7,8]. We have previously reported the potential contribution of a CysLTR1 promoter polymorphism to AIA susceptibility compared to aspirin-tolerant asthma (disease control) [19].…”
Section: Introductionmentioning
confidence: 99%